Implementasi Sistem Pengadaan Material pada SAC dengan Metode Waterfall - Deva Defrina Aldeana; Agustia Hananto; Tukino Tukino; Fitria Nurapriani; Elfina Novalia (Jurnal Teknologi Informasi dan Multimedia, 2025)
Decision support systems in the material procurement process are important solutions to improve operational efficiency and accuracy, especially in retail companies such as SAC (Store Adede Cikampek) which is engaged in the sale of dolls. This study aims to design and build a web-based material procurement system that is able to manage the ordering process, stock recording, verification of incoming goods, and reporting automatically. The system development was carried out using the Waterfall method because its systematic stages are very suitable for handling the material procurement process at SAC which was previously manual and undocumented. With the Waterfall approach, each stage such as needs analysis, design, implementation, testing, to maintenance can be carried out in a structured manner, thus ensuring that the system built is able to overcome problems such as late ordering and errors in recording raw materials. At the implementation stage, this system was developed with various features such as supplier data management, raw material stock management, order history, and periodic report generation. To ensure the effectiveness of the system, testing was carried out using the System Usability Scale (SUS) approach involving twenty respondents from internal operational parties. The evaluation results showed that the developed system succeeded in meeting user needs and increasing the effectiveness of the procurement process by obtaining an average score of 96 which was categorized as "Excellent". This system is also considered easy to use, efficient, and can support the decision-making process in real time. It is expected that the implementation of this system can not only solve the problem of material procurement in SAC, but can also be used as a model for implementing similar systems in similar businesses. This research provides a practical contribution in the development of an integrated information system to support more optimal business processes.